The Effect of Cranberry (Vaccinium macrocarpon) Fruit Extract on VEGF Levels in Wistar Rats (Rattus norvegicus) with Cystitis Model - Muhammad Nur Hidayah Az; Muhammad Andriady Saidi Nasution; Andre Budi; Adrian Joshua Velaro (International Journal Labs, 2025)
Cystitis, often caused by Escherichia coli, triggers inflammation and tissue damage in the bladder. While the anti-adhesion properties of cranberry (Vaccinium macrocarpon) against uropathogenic bacteria are well known, its role in the subsequent healing phase, particularly through modulation of Vascular Endothelial Growth Factor (VEGF), remains poorly understood. This study aims to investigate the effect of cranberry fruit extract on VEGF levels and the degree of histopathological inflammation in a cystitis model. Fosfomycin trometamol is an effective antibiotic for treating urinary tract infections, particularly bacterial cystitis. However, the observed increase in Vascular Endothelial Growth Factor (VEGF) levels during treatment is not a direct effect of the drug but rather a biological response associated with the body’s natural healing process. In cystitis, inflammation and tissue damage in the bladder wall trigger the release of various cytokines and chemokines, including VEGF, which plays a key role in angiogenesis and tissue regeneration. Fosfomycin works by reducing bacterial load and inflammation, thereby allowing the body to enter the active healing phase. During this phase, increased VEGF levels reflect ongoing tissue repair and new blood vessel formation. Therefore, the elevation of VEGF should be interpreted not as a side effect of fosfomycin but as a biological marker of bladder tissue recovery following successful infection clearance.